Globaler Schrott: Raumproduktionen, Destruktionsketten und die sozioökonomischen Strukturen der pakistanischen Schiffsabwrack-Industrie (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2014)
Global Scrap: Global destruction networks, the production of space and socio-economic structures of the Pakistani ship breaking industry. Every year, hundreds of discarded vessels are broken up at South Asian ship breaking yards, including Chittagong in Bangladesh, Alang in India and Gadani in Pakistan. These (waste) flows of end-of-life vessels are being sent from the global north, notably the European Union, to the global south (Indian Subcontinent). This contribution follows the movement of value through global destruction networks by focusing on the Pakistani ship breaking industry at Gadani Beach and linking its significance for the local and national economy to both global processes as well as to labour conditions and environmental problem.
Keywords: Politische Ökonomie; Abfallwirtschaft